Double piezoelectric defects in phononic crystals for ultrasonic transducers. (16th February 2023) - Jo, Soo-Ho; Lee, Donghyu; Yoon, Heonjun; Youn, Byeng D
Abstract: Significant prior research has explored elastic wave-energy localization via defect modes of phononic crystals (PnCs). The integration of defect-introduced PnCs and piezoelectric materials has paved the way for the development of new conceptual products for applications in energy harvesters, wave filters, and ultrasonic sensors. Recently, an attempt has been made to deviate from this paradigm and design an ultrasonic transducer that generates elastic waves. Unfortunately, previous work has been limited to a single-defect situation. Therefore, as an advanced approach, the present work aims to expand the PnC design space into double defects, which will make ultrasonic transducers useful at several frequencies. As a first step, this study targets longitudinal wave generation. To predict the wave-generation performance, a previous analytical model that was built for energy-harvesting purposes under a single-defect situation is modified to be suitable for the present wave-generation purpose under a double-defect situation. Moreover, two parametric studies are executed to analyze how the output responses change based on changes to the input voltage setting and the spacing between the double defects. We hope that these ultrasonic transducers could be potentially applicable for nondestructive testing in structural health monitoring and ultrasonic imaging in medical science.